The political life of medicare / Jonathan Oberlander. - Oberlander, Jonathan (American politics and political economy series, 2003)
Oberlander provides a comprehensive hostory of Medicare politics, from the decades of consensus to debates over Medicare reform. Revealing how Medicare policies have developed over the past several decades this analysis will interest anyone concerned with public policy or healthcare.